2004
DOI: 10.1557/proc-848-ff2.6
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Physical Properties of Ternary Antimonides RE3MSb5 (M = Zr, Hf), U3MSb5 (M = Zr, Hf, Nb), and YbCrSb3

Abstract: Ternary rare-earth transition-metal antimonides RExMySbz have provided fertile ground for discovering materials with varied electrical and magnetic properties such as superconductivity and ferromagnetism. The properties of two important classes of these compounds, RE3TiSb5 and RECrSb3, have been previously investigated. These studies have now been extended to RE3MSb5 (M = Zr, Hf), which show anomalies in their resistivity curves suggestive of electronic transitions, and YbCrSb3, which undergoes long-range magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…For this reason, it was of interest to determine the physical properties of the U 3 MSb 5 series. Following on previously communicated preliminary results [10], we report here the synthesis of the new compounds U 3 MSb 5 (M = Zr, Hf, Nb), their crystal structures, and their transport and magnetic properties.…”
Section: Introductionmentioning
confidence: 89%
“…For this reason, it was of interest to determine the physical properties of the U 3 MSb 5 series. Following on previously communicated preliminary results [10], we report here the synthesis of the new compounds U 3 MSb 5 (M = Zr, Hf, Nb), their crystal structures, and their transport and magnetic properties.…”
Section: Introductionmentioning
confidence: 89%
“…Further experiments to understand these synthetic difficulties are ongoing. For example, results from arc melting reactions with different loading compositions ''SmTi 3 (Sn x Sb 1Àx ) 4 '' (0oxo1 in 0.1 increments) confirmed that this phase does not form beyond xX0.2.…”
Section: Synthesismentioning
confidence: 99%
“…Given that NdTi 3 (Sn 0.1 Sb 0.9 ) 4 and SmTi 3 (Sn 0.1 Sb 0.9 ) 4 were obtained in the presence of excess Sn, these formulas represent the upper limit of Sn solubility. The lower limit of Sn solubility in RETi 3 (Sn x Sb 1Àx ) 4 was not determined, but in light of our inability to prepare ''RETi 3 Sb 4 '' as described above, it is likely that this limit does not extend to x ¼ 0. Further experiments to understand these synthetic difficulties are ongoing.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations